Islamic Architecture: The Correlation Between Cultural Diversity and Mosque Roof Types in Palembang - Zuber Angkasa; Sandra Eka Febrina; Erfan M Kamil (Journal of Islamic Architecture, 2024)
Cultural diversity influences different types of mosque roofs that can be seen even in neighboring districts. This paper examines the differences in mosque dome types in two areas that differ in terms of cultural diversity, namely the Ulu and Ilir areas of Palembang City. The Ulu area is known to have much lower cultural diversity than the Ilir area. The survey was conducted on 50 mosques located in Palembang City and spread across the two regions. We then categorized them into three roof coverings: dome, pyramid, and mixed. We also calculated a diversity index to assess social diversity in each region. Fisher's Exact test was then conducted to determine whether there were differences in dome types by region. It was found that round domes dominated the Ulu region, while pyramids and mixed domes dominated the Ilir region. The paper concludes that the cultural composition in the Ulu, which the Palembang Malay ethnic group dominates, encourages of using of the standard round dome. In contrast, the relatively high cultural diversity in the Ilir leads to the prominence of the identity of the elites who prioritize the pyramid dome and efforts to accommodate multiculturalism with the mixed dome. In particular, this article can encourage efforts to develop theories on architectural dynamics under the influence of cultural diversity in urban and rural areas.